Performance of farmbred Jersey cattle under tropical climatic conditions of Tamil Nadu - A.K. Thiruvenkadan (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Data on production and reproduction performances of 373 Jersey cows born and reared at the Exotic Cattle Breeding Farm, Eachenkottai, Tamil Nadu, India, pertaining to 27 years were collected. They were analysed to study the effects of various non-genetic factors on milk production and reproduction traits. The least-squares means (± SE) for 305-day and total lactation milk yields for all the parities were 1491.6 ± 25.9 and 1560.9 ± 29.9 kg respectively. The averages for lactation length, service period, calving interval and dry period for all lactations were 303.1 ± 4.0, 177.0 ± 10.0, 461.0 ± 9.7 and 160.2 ± 9.7 days respectively. Years grouped into five periods had significant (P